The Representation of Poverty and the Poverty of Representation - Pablo J. Boczkowski (Sociologica)
In this essay I draw upon both my reporting at the Democratic National Convention in Chicago, United States, and my ethnography of the digitization of mental health work in Buenos Aires, Argentina, to examine the representation of poverty and the poverty of representation in contemporary social and political discourse.